Suspension particle size, water quality and geochemical data from Laihianjoki and Sulvanjoki flocculation experiments in April 2021 - Eero Asmala; Peter Österholm; Joonas J Virtasalo (PANGAEA, 2023)
Water samples were collected from the Laihianjoki and Sulvanjoki rivers in April 2021, using a bucket and transferred to 30 L acid-washed containers. The sampling was conducted during springtime, a few weeks after the peak flow caused by snow smelt. The collected river waters were immediately analyzed for pH, temperature, electrical conductivity, and salinity using a WTW Multiline P4 meter. The samples were then transported to the Tvärminne field station of the University of Helsinki, where laboratory experiments began within 24 hours. A large-volume bucket experiment was conducted to study the dynamics of suspended particle size distribution and associated nutrients during the transition from fresh to brackish water conditions. Artificial seawater with salinity of 66.8 g kg-1 was added to river water in an acid-washed basin, while changes in water chemistry and particle size distribution were continuously monitored using a multiparameter water quality sonde and a laser-diffraction particle size analyzer. Additionally, small-volume jar experiments were performed to collect particle samples under controlled conditions using a flocculator apparatus. The collected material was analyzed, and the filtrate was used for further analysis of colored dissolved organic matter. Triplicate samples from flocculator experiments were acidified and analyzed for metal concentrations using an inductively coupled plasma optical emission spectrometer (ICP-OES) and an inductively coupled plasma mass spectrometer (ICP-MS). Filtrate samples were measured for colored dissolved organic matter (CDOM) absorbance and fluorescence using a spectrophotometer and a spectrofluorometer, respectively. Particulate organic carbon (POC) and particulate organic-bound metals were analyzed in filter retentate samples using a mass spectrometer and ICP-MS. Total suspended matter (TSM) was determined by filtering and weighing samples. The apparent particle density was calculated by dividing TSM by volumetric concentrations measured by a laser-diffraction particle size analyzer. However, the density results are biased as particles larger than the detection limit of the instrument are not included in the analysis.